Dietary and genetic regulation of B12 metabolism in sheep - Brassington, Amey H. (2019)
Cobalt (Co) deficiency in sheep can result in poor animal health and performance, ultimately decreasing farm profitability. Development of strategies to improve the health and productivity of Co deficient animals at different stages of the production cycle, but particularly of rapidly growing lambs, is therefore of significant interest and major economic importance to the sheep industry.